Coordination dynamics and cognition - Kelso, J. A. S. (Complex systems in Sport, 2014)
Most theories in cognitive psychology and cognitive neuroscience tend to view the mind in terms of fairly static representations. Symbolic representation, by definition, is discrete and time independent. Yet many perceptual and cognitive processes unfold in time. Indeed, in many processes - such as perceiving, learning, remembering, forgetting, decision-making and moving - time and timing are essential. Over the last few decades, a new foundation for understanding spatiotemporally organized behaviour on multiple levels has emerged, called coordination dynamics. Coordination dynamics is both a theory and a research programme. In its mature form, it contains two complementary conceptual themes. One concerns the cooperative and competitive mechanisms that give rise to the spontaneous formation of patterns and pattern change in complex cognitive and social systems. The other deals with how information is created de novo in such complex systems and how it modulates and is modulated by spontaneous, pattern forming processes. Dynamics is the language of understanding and transcends levels bridging individual and collective processes. Dynamics, however, is not a panacea. In every case, dynamical tools must be filled with conceptual content. It is not enough to talk about the 'dynamical systems approach' to motor control, development, cognition, and so forth, without the crucial concepts and methods of self-organization, identifying meaningful pattern variables, and informational specificity in the form of parameters of the coordination dynamics. Although every system is different, what we learn about one may aid in understanding another. Indeed, such an approach led to the recognition of universality and mesoscopic protectorates in coordination dynamics. Although the theoretical concepts of self-organizing dynamical systems now enjoy some popularity in the social, behavioural, cognitive and brain sciences, their usage is still quite restricted and still largely metaphorical - though times, it must be said, are changing. One reason for the inertia was that the tools are difficult to learn and require a degree of mathematical sophistication. Their implementation in real systems is nontrivial, requiring a different approach to experimentation and observation. Another reason is that coordination dynamics (and the dynamical perspective in general) are often cast (or cast themselves) in opposition to more conventional theoretical approaches, instead of as an aid to understanding. On a personal note, the author has been invited on many occasions over the years to write papers on 'programmes' versus 'dynamics'. Selforganizing dynamics tends to emphasize decentralization, collective decision making, spontaneous and cooperative behaviour among many interacting elements. Conventional cognitive psychology tends to focus on individual psychological processes such as intention, perception, attention, memory, action, and so on, as if they were clearly separable aspects of the goal-directed coordination of living things. Yet, as evidence and theory now show, processes that we associate with meaningful information such as intending, perceiving, attending, deciding and remembering - as well as spontaneous self-organizing processes - prove to be essential, coexisting aspects of the coordination dynamics of cognition. Representation and dynamics are complementary: two sides of the same coin.